Survival status and predictors of mortality among neonates admitted to neonatal intensive care unit at Bichena Primary Hospital, Northwest Ethiopia. A retrospective cohort study - Enawgaw, Anley Shiferaw; Belay, Debas; Nigate, Alehegn; Yeshiwas, Almaw Genet; Shumet, Tesfaye; Endalew, Bekalu; Bishaw, Keralem Anteneh (Frontiers in Pediatrics, 2025)
BackgroundDespite progress in reducing neonatal mortality rates in Ethiopia, the country still has a high neonatal mortality rate compared with the global average. Primary hospitals are critical in delivering basic neonatal care, particularly in rural areas. However, data on neonatal mortality and contributing factors in these settings are scarce. This study aimed to determine the survival status and predictors of neonatal mortality among neonates admitted to Bichena Primary Hospital, Northwest Ethiopia.MethodsA retrospective cohort study was conducted among 638 neonates admitted to the Bichena Primary Hospital neonatal intensive care unit from January 1, 2021, to April 30, 2023. Neonates were selected via a consecutive sampling method. Data were collected from medical records using a pretested checklist. A Kaplan–Meier survival curve was used to estimate the neonatal survival time, and a Cox proportional hazard regression model was used to identify independent predictors of neonatal mortality.ResultsOf the 638 neonates followed, 21.5% died during the study period. The overall incidence rate of death was 66.69 per 1,000 neonate days. Hypothermia, birth injury, perinatal asphyxia, preterm birth, maternal history of abortion, low birth weight, and neonatal hypoglycemia were independent predictors of neonatal mortality.Conclusion and recommendationThe study found a high rate of neonatal mortality, exceeding rates reported in other regions of Ethiopia. Most predictors were preventable and treatable. Therefore, early identification of obstetric complications, immediate interventions and postnatal care are crucial to reduce neonatal mortality and enhance overall neonatal outcomes.